Projeto conceitual de máquina para corte de palmito: uma proposta de melhoria do processo de beneficiamento do palmito em tolete - LOPES, Leandro Ferreira (2019)
The objective of this work is propose a mechanical equipment for cutting palm hearts in 9 cm sticks, aiming to improve the process of palm heart factories in this stage (cut of the palm hearts in sticks, since the cut of palm hearts in sticks is produced per unit). In addition to give more comfort to the employee and increasing productivity in this process. Justifying use in this work, the Product Development Process (PDP) to propose a product that improves the palm heart beneficiation process. For this project, the following tools were used: Project Model Canvas, QFD (Quality Function Deployment), Functional Project, Morphological Matrix and 3D digital modeling with Revit software. In addition, tests were carried out with a similar equipment to estimate the machine's operating time and the results were compared with the performance of products on the market and costs were raised for the manufacture of equipment called PCP-3L. At the end of this study, we obtained a concept of equipment with a satisfactory performance and low cost compared to competitors in the market.